A novel approach to quantitative characterisation of key volatile aroma compounds in strawberry (Fragaria × ananassa) using stable isotope dilution assay and HS-SPME-GC-MS for flavour-driven breeding - Dilmini Hettiarachchi; Heather E. Smyth; Craig M. Hardner; Daniel Cozzolino; Jodi Neal; Katie M. O'Connor; Thoa T.L. Nguyen (Food Chemistry, 2026)

From field to sky: measurement and modeling of transgenic switchgrass pollen dispersal in the atmosphere - Manu Nimmala; Hope A. Gruszewski; Regina Hanlon; Landon Bilyeu; Tyler Newton; Jessica Stockdale; Reginald J. Millwood; Charles Neal Stewart; Craig W. Powers; Shane D. Ross; Hosein Foroutan; David G. Schmale III (Environmental Monitoring and Assessment, 2026)
Accurate tracking and measurement of pollen dispersal in the atmosphere are essential for assessing cross-pollination risks, particularly in the case of genetically engineered (GE) crops. We conducted a series of unique release-recapture field studies with GE switchgrass in Oliver Springs, TN, USA. Two hundred transgenic switchgrass plants ( Panicum virgatum L. “Performer”) were planted at the center of a clear-cut field, with one block of 100 plants expressing orange fluorescent protein (OFP) under a switchgrass ubiquitin promoter (PvUBI1) and another block of 100 plants expressing OFP driven by a maize pollen-specific promoter (Zm13). Pollen was sampled from the atmosphere using fixed (ground-based) and mobile (drone-based) sampling devices at different distances from the source field, with Lagrangian stochastic dispersal simulations run for sampling periods using high-resolution wind measurements. The pollen emission rate was estimated by combining simulated and measured pollen concentrations, and strong diurnal trends were observed. Diurnal emission rate trends were positively correlated with wind speed, temperature, and vapor pressure deficit, while negatively correlated with relative humidity. In low-wind meandering conditions, incorporating changing wind direction into the dispersal modeling improved pollen emission rate estimation and model-measurement comparisons. This study assesses the effectiveness of high- and low-volume pollen samplers in relation to source strength up to 1 km from the source, enhancing understanding of pollen measurement techniques. Additionally, it is a proof-of-concept for drone-based pollen sampling and GMO pollen tracking using fluorescence measurements. Results from our experiments have significant implications for cross-pollination risk assessment, prediction, and management of airborne allergens.

Shifting paradigms in restoration of the world's coral reefs - Madeleine J. H. van Oppen; Ruth D. Gates; Linda L. Blackall; Neal Cantin; Leela J. Chakravarti; Wing Y. Chan; Craig Cormick; Angela Crean; Katarina Damjanovic; Hannah Epstein; Peter L. Harrison; Thomas A. Jones; et al. (Global Change Biology, 2017)
Many ecosystems around the world are rapidly deteriorating due to both local and global pressures, and perhaps none so precipitously as coral reefs. Management of coral reefs through maintenance (e.g., marine‐protected areas, catchment management to improve water quality), restoration, as well as global and national governmental agreements to reduce greenhouse gas emissions (e.g., the 2015 Paris Agreement) is critical for the persistence of coral reefs. Despite these initiatives, the health and abundance of corals reefs are rapidly declining and other solutions will soon be required. We have recently discussed options for using assisted evolution (i.e., selective breeding, assisted gene flow, conditioning or epigenetic programming, and the manipulation of the coral microbiome) as a means to enhance environmental stress tolerance of corals and the success of coral reef restoration efforts. The 2014–2016 global coral bleaching event has sharpened the focus on such interventionist approaches. We highlight the necessity for consideration of alternative (e.g., hybrid) ecosystem states, discuss traits of resilient corals and coral reef ecosystems, and propose a decision tree for incorporating assisted evolution into restoration initiatives to enhance climate resilience of coral reefs.

EGFR Targeted Theranostic Nanoemulsion for Image-Guided Ovarian Cancer Therapy - Srinivas Ganta; Amit Singh; Praveen Kulkarni; Amanda W. Keeler; Aleksandr Piroyan; Rupa R. Sawant; Niravkumar R. Patel; Barbara Davis; Craig Ferris; Sara O’Neal; William Zamboni; Mansoor M. Amiji; et al. (Pharmaceutical Research, 2015)

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)